Fabrication of Fe-6.5wt%Si Ribbons by Melt Spinning Method on Large Scale. (4th May 2015) - Liang, Y. F.; Wang, S.; Li, H.; Jiang, Y. M.; Ye, F.; Lin, J. P.
Abstract : Melt spinning method has been widely applied for fabrication of Fe-based amorphous/nanocrystalline ribbons in industry. Compared with Fe-based amorphous/nanocrystalline alloys, Fe-6.5wt%Si high silicon steel is of low cost and has comparable excellent soft magnetic properties. Due to higher melting point and absence of supercooled liquid region, fabrication of Fe-6.5wt%Si ribbons is very hard and is only on lab scale. In this paper, we report that large scale fabrication of Fe-6.5wt%Si ribbons was successful and microstructures, ordered structures, and mechanical and soft magnetic properties of the ribbons were investigated. Due to rapid solidification rate, the ribbons were of ultrafine grains, and low degree of order and exhibited some extent of bending and tensile ductility. After heat treatment, excellent soft magnetic properties were obtained. Due to near-zero magnetostriction, the ribbons are promising to be used in electric devices with high frequencies where low noises are required.